The Effect of Using Buzz Group and Talking Chips Technique on Students’ Speaking Ability at Senior High School - Erika Sinambela; Poster Sagala; Arsen Nahum Pasaribu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This study deals with the effect of using controlled Buzz Group technique and Talking Chips technique on students’ speaking ability. The objectives are to find out the effect of using Buzz Group technique and Talking Chips technique on students’ speaking ability and which technique is the most effective one. The method that was used in this research was quantitative through quasi-experimental research that incriminating three classes were experimental class 1, experimental class 2 and control class, in the experimental class the writer applied Buzz Group technique and Talking Chips technique while in controlled class applied without treatment. The population of this study was the eleventh-grade students of SMA Kristen Kalam Kudus Medan. The researcher used 75 students as the sample. The sample of this research was taken by using cluster sampling technique, 25 from XI-1 and 25 XI-2 as experimental class and 25 from XI-3 as controlled class. To obtain the data the researcher used speaking oral test. The instruments used to gather the data were students’ pre-test & post-test scores that were calculated and analyzed by using IBM SPSS 23.0. These tests consisted of two types, namely pre-test and post-test. The result of analyzing the data, the mean score for pre-test in experimental class one (Buzz Group technique) is 60.80 and the mean score for post-test is 79.60. The mean score for pre-test in experimental class two (Talking Chips technique) is 50.12 and the mean score for post-test is 74.24. The mean score for pre-test in control class is 66.76 and the mean score for post-test is 74.44. As the result of the ANOVA test, P= 0.00 < 0.05 or F count = 23.59 > F table = 2.28. It means that hypothesis alternative (Ha) was accepted while the null hypothesis (Ho) was rejected. In conclusion, the using of Talking Stick technique and Buzz Group technique is modestly effective on students’ speaking ability of asking and giving opinion of eleventh grade at SMA Kristen Kalam Kudus Medan academic year 2022/2023 and Talking Chips technique is more effective than Buzz Group technique in teaching speaking skill. Based on the explanation above, this research can be chosen as one alternative technique in teaching speaking.